2022
DOI: 10.3389/fnagi.2022.884741
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Emotion Regulation in Mild Cognitive Impairment Individuals Combined With Depressive Disorder: A Neural Mechanism Study

Abstract: Depression increases the risk of progression from mild cognitive impairment (MCI) to dementia, where impaired emotion regulation is a core symptom of depression. However, the neural mechanisms underlying the decreased emotion regulation in individuals with MCI combined with depressive symptoms are not precise. We assessed the behavioral performance by emotion regulation tasks and recorded event-related electroencephalography (EEG) signals related to emotion regulation tasks simultaneously. EEG analysis, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
(79 reference statements)
1
7
0
Order By: Relevance
“…VCI group was defined as MOCA scores less than 24. When the critical score is 24, MoCA has good specificity and sensitivity, which is supported by many studies based on Chinese population (Tsai et al, 2012;Chen et al, 2016;Liu et al, 2022); therefore, patients with a total score of <24 were diagnosed with cognitive impairment (Pugh et al, 2018). All patients included in this study were acute ischemic stroke patients, and for the patients from cognitive impairment group, all of them had a Hachinski Ischemic Scale greater than 7, which is consistent with the criteria of VCI.…”
Section: Assessment Of Neurocognitionsupporting
confidence: 69%
“…VCI group was defined as MOCA scores less than 24. When the critical score is 24, MoCA has good specificity and sensitivity, which is supported by many studies based on Chinese population (Tsai et al, 2012;Chen et al, 2016;Liu et al, 2022); therefore, patients with a total score of <24 were diagnosed with cognitive impairment (Pugh et al, 2018). All patients included in this study were acute ischemic stroke patients, and for the patients from cognitive impairment group, all of them had a Hachinski Ischemic Scale greater than 7, which is consistent with the criteria of VCI.…”
Section: Assessment Of Neurocognitionsupporting
confidence: 69%
“…Health‐related exclusion criteria generally helped to ensure a sample that could safely complete a bout of moderate to vigorous intensity aerobic exercise. Exclusion of left‐handed individuals, mental health conditions, and cognitive impairment was particularly important in cutting potential sources of variation in emotional brain processing, as well (Brookshire & Casasanto, 2012; Bylsma et al, 2008; Costanzo et al, 2015; Li et al, 2020; Liu et al, 2022). Exclusion of individuals with probable obstructive sleep apnea was performed to exclude those with characteristically worsened sleep, since wrist actigraphy‐based sleep data were also analyzed for the present sample (Alfini et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have confirmed that emotion regulation is impaired in MCI ( Bora and Yener, 2017 ; Liu et al, 2022 ), mainly focusing on negative emotions and that the recognition of positive faces, such as joy, happiness, and hope, is no different from healthy older adults ( McCade et al, 2013 ; Elferink et al, 2015 ; Barbieri et al, 2022 ). This seems to suggest that MCI retains the “positive effect.” In addition, based on scholars’ proposal of the dual competition models, it is known that emotions and cognitions compete with each other, and the process largely depends on attentional capture ( Pessoa, 2009 ).…”
Section: Introductionmentioning
confidence: 98%